Development of an Automated Three-Phase Distribution Box System - Zemri, Nurul Syuhadah (Universiti Teknologi PETRONAS, 2016)
Nowadays, most electrical appliances require continuous power supply. For domestic use, crucial appliances such as refrigerator, aquarium and alarm system highly depend upon the continuity of power supply. However, if they are left without electricity due to power outage or blackouts caused by internal or external disturbance, the discontinuity of power supply could be a critical issue to some involving party. Blackouts may be due to short circuit, fault or the overloading of electricity mains. During power outage, Residual Current Device (RCD) detects fault currents from live to the neutral wire within circuit and will trip to prevent shock. This circumstance can increase safety when a house is left unoccupied. Be that as it may, the power will remain switched off until manually reset by man. Thus, an Automated Three-phase Distribution Box System is being developed to overcome tripping problem.